The Spatial Distribution of Robberies In Makassar City - Abidin, Muhammad Rais; Sideng, Uca; Arfan, Amal; Syarif, Erman; Dirawan, Gufran Darma; Azhim, Muhamad Ihsan (UNM Geographic Journal, 2018)
This study aims to identify the spatial distribution of robberies in Makassar city by using crime mapping (crime analysis) through Geographic Information System in order to find a novel solution to deal with them. This study employs spatial analysis and snowball sampling to analyze and collect the data. The results show that the spatial pattern of robberies between 2015 and 2016 was cluster consisted of three categories high, medium and low crime density, and it also reveals that there was significant increase the number of robberies from 76 to 140 cases in 2015 and 2016 respectively. In addition, based on the time series analysis, it shows that in 2015 the high crime occurred in August, September, and April meanwhile the low crime was in January, October, November, and December. In 2016, the high crime was in March, September and October while medium crime happened mostly in January, April, Mei, June, July and August, and there was not low crime recorded in 2016.